2020
DOI: 10.1021/acsinfecdis.0c00547
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Endogenous Antibody Recruitment to the Surface of the Pathogen Enterococcus faecium

Abstract: For the foreseeable future, conventional small molecule antibiotics will continue to be the predominant treatment option due to wide patient coverage and low costs. Today, however, there is already a significant portion of patients that fail to respond to small molecule antibiotics and, according to the Centers for Disease Control and Prevention, this number is poised to increase in the coming years. Therefore, this rise in drug resistant bacteria must be countered with the development of nontraditional therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

7
2

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Our group, and others, previously showed that synthetic acyl-acceptor strands modified with an N-terminal fluorophore are well tolerated by cell wall crosslinking enzymes (PBPs and Ldts). [37][38][39][40][41][42][43] We envisioned that a similar tolerability would enable the structure-activity relationship of srtA. As wildtype S. aureus displays pentaglycine cross-bridge (G5) appended to its 3 rd position lysine sidechain, we first sought to determine the importance of the glycine cross-bridge length.…”
Section: Resultsmentioning
confidence: 99%
“…Our group, and others, previously showed that synthetic acyl-acceptor strands modified with an N-terminal fluorophore are well tolerated by cell wall crosslinking enzymes (PBPs and Ldts). [37][38][39][40][41][42][43] We envisioned that a similar tolerability would enable the structure-activity relationship of srtA. As wildtype S. aureus displays pentaglycine cross-bridge (G5) appended to its 3 rd position lysine sidechain, we first sought to determine the importance of the glycine cross-bridge length.…”
Section: Resultsmentioning
confidence: 99%
“…Dalesandro and Pires recently reported synthetic peptidoglycans conjugated to antibody‐recruiting molecules, which were designed to be incorporated by the cell wall of live Enterococcus faecium and vancomycin‐resistant bacterial strains. Treatment with the conjugates led to covalent display of the ABDs, subsequent antibody‐recruitment, and macrophage phagocytosis [19] …”
Section: Recent Advances In the Design Of Antibody‐recruiting Moleculesmentioning
confidence: 99%
“…Treatment with the conjugates led to covalent display of the ABDs, subsequent antibody-recruitment, and macrophage phagocytosis. [19] Another limitation of early generation ARMs is modest affinity between endogenous antibodies and the ABD. For example, while relatively simple ABDs like DNP are bound by a significant percentage of serum antibodies, the affinity of these interactions can be low (K D ~10 À 4 -10 À 6 M).…”
Section: Recent Advances In the Design Of Antibody-recruiting Moleculesmentioning
confidence: 99%
“…Instead, we envisioned that administration of a synthetic stem peptide analog conjugated to a NIR fluorophore would circumvent this challenge (Figure 4A). We [41][42][43][44] , and others [45][46][47] , have shown that treatment of bacterial cells with stem peptide analogs also result in their incorporation the PG by PG-related transpeptidases (Figure 4B). The principal advantage of stem peptide analogs is that our laboratory previously showed that the N-terminus of a tetra-or penta-stem peptide analog demonstrates tolerability to large chemical modifications.…”
Section: Introductionmentioning
confidence: 99%